Sea Surface Height Measurement Using a GNSS Wave Glider. Issue 11 (10th June 2018) - Penna, Nigel T.; Morales Maqueda, Miguel A.; Martin, Ian; Guo, Jing; Foden, Peter R.
Abstract: To overcome spatial and temporal limitations of sea surface height instruments such as tide gauges, satellite altimetry, and Global Navigation Satellite Systems (GNSS) buoys, we investigate the use of an unmanned, self‐propelled Wave Glider surface vehicle equipped with a geodetic GNSS receiver. Centimetric precision instantaneous sea surface height measurement is demonstrated from a 13‐day deployment in the North Sea, during which the glider traversed a track of about 600 km. Ellipsoidal heights were estimated at 5 Hz using kinematic GNSS precise point positioning and, after correcting for tides using the Finite Element Solution 2014b model and for the geoid using the Earth Gravitational Model 2008, hourly dynamic ocean topography measurements agreed with those from the UK Met Office Forecasting Ocean Assimilation Model‐Atlantic Margin Model 7 to 6.1‐cm standard deviation. Conversely, on correcting for the tides and dynamic ocean topography, 5.1‐cm standard deviation agreement with Earth Gravitational Model 2008 at its North Sea spatial resolution was obtained. Hourly measurements of significant wave height agreed with the WAVEWATCH III model and WaveNet buoy observations to 17 and 24 cm (standard deviation), respectively, and dominant wave periods to 1.4 s. These precisions were obtained in winds gusting up to 20 m/s. Plain Language Summary: High‐rate (subsecond), continuous sea surface height measurement is demonstrated using an unmanned, self‐propelled, surf‐board sized Wave Glider surface vehicle equipped with a Global Navigation Satellite Systems (GNSS) receiver and antenna. GNSS data postprocessing determined centimetric precision sea surface heights over a user‐defined, remotely piloted route of about 600 km in the North Sea over 13 days, measuring the waves and the variation in the sea surface from the geoid (the surface it would occupy due to Earth's gravity alone) caused by winds and currents, plus tides. Our portable, bespoke, in situ measurement method is applicable globally, subject to sufficient light for on‐board instrumentation solar power, 10‐m water depth, and GNSS signal tracking (outages attributed to waves breaking over the antenna arose when local winds became near gale force). The GNSS Wave Glider overcomes sea surface height measurement spatial resolution limitations of coastline‐based tide gauges, single location GNSS buoys and ships following fixed routes, and the temporal and spatial resolution limitations of radar measurements from satellites. Such sea surface height measurements are needed for studies on coastal erosion; for the transport of sediments, pollutants, and heat; for understanding coastal ecosystems and climate change; and for coastal structural design and navigation management. Key Points: GNSS Wave Glider measures instantaneous sea surface heights with centimetric precision in the North Sea, in winds gusting up to 20 m/s Hourly dynamic ocean topography measurements agree with high‐resolution assimilation model values to 6.1 cm standard deviation Measured significant wave heights agree with the WAVEWATCH III model and wave buoy data to 17–24 cm and dominant wave periods to 1.4 s